2020
DOI: 10.1016/j.dld.2020.09.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients with inflammatory bowel disease: A systematic review of clinical data

Abstract: Background Great efforts by the scientific community are rapidly expanding the evidence on the clinical interplay between Covid-19 and inflammatory bowel disease (IBD). Aims We performed a systematic review of the literature on published Covid-19 cases occurring in patients with IBD. Methods PubMed Central/Medline and Embase were systemically searched for records up to May 31, 2020. Results 13 cohort studies and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 30 publications
4
63
0
1
Order By: Relevance
“…The low frequency of COVID‐19 has been reported earlier in multiple uncontrolled studies from Spain, 24 Hong Kong, 25 Taiwan, 25 and Italy 26 . A systemic review also showed the same result 27 . However, our study also compared these data with a large number of non‐IBD controls.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The low frequency of COVID‐19 has been reported earlier in multiple uncontrolled studies from Spain, 24 Hong Kong, 25 Taiwan, 25 and Italy 26 . A systemic review also showed the same result 27 . However, our study also compared these data with a large number of non‐IBD controls.…”
Section: Discussionsupporting
confidence: 82%
“…6 Some studies even suggested that patients with IBD on treatment may have less severe COVID-19. 27 Although there is not enough data regarding the safety or adverse event profile with thiopurines in patients with IBD in the context of COVID-19 in the literature, our studydue to its small sample size and observational design-does not support the use of these agents in the context of SARS-CoV-2 infection either.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Table 1 (Tab. 1) (References in Table 1: Balaphas et al, 2020[ 2 ]; Boettler et al, 2020[ 3 ]; Colmenero et al, 2021[ 7 ]; Ding et al, 2004[ 8 ]; Elli et al, 2020[ 10 ]; Garland et al, 2020[ 12 ]; Jothimani et al, 2020[ 20 ]; Lee-Archer et al, 2020[ 22 ]; Macaluso and Orlando, 2020[ 24 ]; Monteleone and Ardizzone, 2020[ 26 ]; Nabil et al, 2020[ 27 ]; Onder et al, 2020[ 28 ]; Portincasa et al, 2020[ 30 ]; Rana, 2020[ 32 ]; RECOVERY Collaborative Group et al, 2020[ 33 ]; Wang et al, 2020[ 36 ]; Wu et al, 2020[ 38 ]; Yang et al, 2010[ 40 ]; Yang et al, 2019[ 41 ]; Yang et al, 2020[ 42 ]) shows the current updated status of COVID-19 in gastroenterology, liver injury, endoscopy, inflammatory bowel diseases (IBD), and imaging.…”
Section: Covid‐19 and Its Effects On The Digestive Systemmentioning
confidence: 99%
“…Our initial experience of COVID-19 has suggested that the medications used for patients with IBD do not seem to confer an increased risk of infection, severity, or poorer outcomes. 7 It might not be possible to currently confirm that the same is true for the new variants. Moreover, further mutations of SARS-CoV-2 are likely to develop in the future, which might lead to altered infectivity, virulence, and severity.…”
mentioning
confidence: 98%